INTERDISCIPLINARY COMMUNICATION - AS AN EFFECTIVE METHOD THAT DIRECTS THE READER TO INDEPENDENT THINKING - Abdurahmonova Barno Muhammadjonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article discusses the problems of students of a secondary school in the analysis of classical works in Literature lessons. As a support in solving these problems, methods of using interdisciplinary communication were recommended as a solution in the analysis of Muqimi works given in the school textbook-complex “literature”.